Improving child nutrition and development through community-based childcare centres in Malawi – The NEEP-IE study: study protocol for a randomised controlled trial - Gelli, Aulo; Margolies, Amy; Santacroce, Marco; Sproule, Kathryn; Theis, Sophie; Roschnik, Natalie; Twalibu, Aisha; Chidalengwa, George; Cooper, Amrik; Moorhead, Tyler; Gladstone, Melissa; Kariger, Patricia; et al. (Springer, 2017)
Background The Nutrition Embedded Evaluation Programme Impact Evaluation (NEEP-IE) study is a cluster randomised controlled trial designed to evaluate the impact of a childcare centre-based integrated nutritional and agricultural intervention on the diets, nutrition and development of young children in Malawi. The intervention includes activities to improve nutritious food production and training/behaviour-change communication to improve food intake, care and hygiene practices. This paper presents the rationale and study design for this randomised control trial. Methods Sixty community-based childcare centres (CBCCs) in rural communities around Zomba district, Malawi, were randomised to either (1) a control group where children were attending CBCCs supported by Save the Children’s Early Childhood Health and Development (ECD) programme, or (2) an intervention group where nutritional and agricultural support activities were provided alongside the routine provision of the Save the Children’s ECD programme. Primary outcomes at child level include dietary intake (measured through 24-h recall), whilst secondary outcomes include child development (Malawi Development Assessment Tool (MDAT)) and nutritional status (anthropometric measurements). At household level, primary outcomes include smallholder farmer production output and crop-mix (recall of last production season). Intermediate outcomes along theorised agricultural and nutritional pathways were measured. During this trial, we will follow a mixed-methods approach and undertake child-, household-, CBCC- and market-level surveys and assessments as well as in-depth interviews and focus group discussions with project stakeholders. Discussion Assessing the simultaneous impact of preschool meals on diets, nutrition, child development and agriculture is a complex undertaking. This study is the first to explicitly examine, from a food systems perspective, the impact of a preschool meals programme on dietary choices, alongside outcomes in the nutritional, child development and agricultural domains. The findings of this evaluation will provide evidence to support policymakers in the scale-up of national programmes.